Euro area business cycles in turbulent times: convergence or decoupling? - Benjamin Klaus; Filippo Ferroni (European Central Bank (ECB), 2015)
We study the business cycle properties of the four largest euro area economies in the wake of the recent recession episodes. The analysis is based on the factors estimated from a multi-country and multi-sector data-rich environment. We measure alikeness of business cycles by studying the synchronization of up and down phases, the convergence properties of country fluctuations towards the euro area cycles and the contribution of the euro area factor to national GDP volatilities. While the economic fluctuations of the four euro area member states were similar before the global financial turmoil, we gather compelling evidence of an asymmetric behaviour of Spanish fluctuations relative to the euro area one.
Keywords: C51; E32; O52; 330; Hierarchical factor models; International business cycles; Synchronization and Convergence ECB